Development of superparaelectric BaTiO3 system ceramics through heterovalent Mn-Nb co-doping for DC-bias free dielectrics. (1st November 2022) - Sapkota, Piyush; Fujii, Ichiro; Kim, Sangwook; Ueno, Shintaro; Kuroiwa, Yoshihiro; Wada, Satoshi
Abstract: BaTi(1–2 x ) Mn x Nb x O3 ceramics with 0 ≤ x ≤ 0.10 were fabricated and the crystal structure, microstructure, dielectric, and ferroelectric properties were investigated. The samples with x ≥ 0.06 showed a pseudo-cubic symmetry in a wide temperature range from −150 °C to 200 °C but exhibited domain structures and a non-linear polarization–electric field response. The dielectric constant for these samples exhibited a comparatively flat response with temperature. The DC-bias dependence of the dielectric constant improved drastically from the samples with x = 0.06. A qualitative model of chemical grain size (CGS), defined by the distance between the co-dopant ions, was proposed which expressed the phonon propagation length in a wide temperature range and thus induced superparaelectricity in the ceramics. A critical CGS = 810 pm was determined geometrically for the sample with x = 0.06 such that samples with x ≥ 0.06 were superparaelectric in nature.